PENGARUH VOLUME URIN TERHADAP PEMERIKSAAN SEDIMEN URIN PADA PASIEN INFEKSI SALURAN KEMIH (ISK) - Tadjuddin Naid; Fitriani Mangerangi; Muldhaniah Arsyad (Fakultas Farmasi UMI, 2015)
The research about effect of urine volume to urine sediment examination in patient with Urinary Tract Infection (UTI) at Wahidin Sudirohusodo hospital was performed. This research aimed to find out the volume urine effect to urine sediment examination in Urinary Tract Infection (UTI) so as to improve the diagnostic a laboratory. This research used laboratorial eksperimental method with total samples are 30 consist of 13 male (43,3%) and 17 female (56,7%). Microscopically sample examination used Shih-Yung method with during urine with comparative volume 12 ml, 10 ml, and 8 ml. This research showed mean total urine sediment in volume 12 ml (leukocyte 37,75/μL; erythrocyte 7,77/μL; epithelial cells 7,96/lfv; bacteria 5,15/lfv) in volume 10 ml (leukocyte 22,67/ μL; erythrocyte 4,48/ μL; epithelial cells 4,35/lfv; bacteri 3,88/lfv) in volume 8 ml (leukocyte 12,20/μL; erythrocyte 2,16/μL; epithelial cells 2,50/lfv; bacteria 2,08/lfv) from One Way Anova statistic test get P value = 0,000 (